2022
DOI: 10.1073/pnas.2200205119
|View full text |Cite|
|
Sign up to set email alerts
|

The oxygen initial dip in the brain of anesthetized and awake mice

Abstract: Significance Sensory stimulation generates a robust decrease in oxygen concentration (pO 2 initial dip) in brain tissue of anesthetized cats and rodents. This dip reports local activation of neurons much better than the delayed pO 2 increase associated with functional hyperemia. Here, we reinvestigated the issue in animals that recovered from acute surgery using two-photon lifetime microscopy. Targeting a distinct neuronal network that is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…Notably, the amplitude and the timing of BLI response differed between awake and KX-anesthetized mice (fig. S6), supporting the notion that anesthesia dampens tissue P o 2 and functional hyperemia dynamics ( 13 , 14 ).…”
Section: Green Enhanced Nano-lantern Can Detect Oxygen In Mouse Cortexsupporting
confidence: 69%
“…Notably, the amplitude and the timing of BLI response differed between awake and KX-anesthetized mice (fig. S6), supporting the notion that anesthesia dampens tissue P o 2 and functional hyperemia dynamics ( 13 , 14 ).…”
Section: Green Enhanced Nano-lantern Can Detect Oxygen In Mouse Cortexsupporting
confidence: 69%
“…Here, we address the role of CO 2 produced by neuronal activation in generating NVC in layer 2/3 of the barrel cortex. All of our experiments were performed in chronic rather than acute preparations, as they preserve better brain metabolism 7 . We introduce briefCO 2 , a specific short and strong CO 2 stimulation that triggers sharp vascular and cellular responses in brain vessels and cells, and allows repetitive applications.…”
Section: Discussionmentioning
confidence: 99%
“…Initial measurements of partial pressure of oxygen (pO2) with Clark electrodes, performed in the brain parenchyma of anesthetized animals with acute craniotomies [3][4][5] , reported that sensory stimulation generated local pO2 dips, the timing of which was compatible with a triggering role in NVC 6 . This hypothesis was however recently questioned, as the pO2 dip disappeared in chronically-prepared awake mice, i.e., more akin to physiological conditions 7 . The triggering role of oxygen in NVC is therefore unlikely, even though one study reported that local application of O2 scavengers could generate a pO2 dip and an increase in blood flow 8 .…”
Section: Introductionmentioning
confidence: 99%
“…In the brain, state-of-the-art measurements of pO 2 have recently challenged the controversial view that hyperemia-induced increases in local pO 2 are preceded by an initial dip ( Kim et al, 2000 ; Logothetis, 2000 ; Buxton, 2001 ; Lindauer et al, 2001b ; Vanzetta and Grinvald, 2001 ; Thompson et al, 2003 , 2004 ; Kasischke et al, 2004 ; Dunn et al, 2005 ; Offenhauser et al, 2005 ; Sirotin et al, 2009 ; Hu and Yacoub, 2012 ; Ma et al, 2016 ; Aydin et al, 2022 ), which has been postulated to be driven by increased neuronal metabolism during activity. Instead, recent data support the view that O 2 tension is initially unchanged by the initiation of neuronal activity and is then followed by a large influx in O 2 during hyperemia ( Aydin et al, 2022 ).…”
Section: The Hallmarks Of Emsmentioning
confidence: 99%
“…In the brain, state-of-the-art measurements of pO 2 have recently challenged the controversial view that hyperemia-induced increases in local pO 2 are preceded by an initial dip ( Kim et al, 2000 ; Logothetis, 2000 ; Buxton, 2001 ; Lindauer et al, 2001b ; Vanzetta and Grinvald, 2001 ; Thompson et al, 2003 , 2004 ; Kasischke et al, 2004 ; Dunn et al, 2005 ; Offenhauser et al, 2005 ; Sirotin et al, 2009 ; Hu and Yacoub, 2012 ; Ma et al, 2016 ; Aydin et al, 2022 ), which has been postulated to be driven by increased neuronal metabolism during activity. Instead, recent data support the view that O 2 tension is initially unchanged by the initiation of neuronal activity and is then followed by a large influx in O 2 during hyperemia ( Aydin et al, 2022 ). Furthermore, classic positron-emission tomography experiments have convincingly demonstrated that activity-evoked increases in neuronal activity are not associated with significant increases in O 2 consumption but are accompanied by increased glucose utilization—leading to the hypothesis that aerobic glycolysis predominates as a mechanism to rapidly supply energy during sudden increases in brain activity ( Raichle and Mintun, 2006 ).…”
Section: The Hallmarks Of Emsmentioning
confidence: 99%